PUBLIC PERCEPTION REGARDING THE SELECTION OF CHEMICAL AND TRADITIONAL MEDICINE FOR HYPERCHOLESTEROLEMIA IN SUKOREJO GIRITIRTO WONOGIRI - Atikah, Nur; Murwati; Batrisyia, Amalia (Jurnal Jamu Kusuma, 2024)
Hypercholesterolemia can trigger cardiovascular disease, and treatment options use chemical drugs and traditional medicine. The aim of the research was to determine public perceptions regarding the choice of chemical drugs and traditional medicines for hypercholesterolemia in the Sukorejo Giritirto Wonogiri area. The research method used a descriptive cross-sectional approach, with a purposive sampling technique for respondents who met the inclusion criteria, namely aged > 17 years, had a history of hypercholesterolemia and had used chemical drugs, traditional medicines, and a combination of chemical and traditional medicines. Meanwhile, the exclusion criteria are respondents who are not willing to take part in the research. The sample obtained was 80 people. The 24-question questionnaire has been tested for Pearson product moment validity with a p value <0,05, and a Cronbach's Alpha reliability value of 0,826. Data analysis uses percentage calculations, and the median value as a cut-off point. The perception assessment criteria are positive perception ≥ median value and negative perception ≤ median value. The results showed that 51,25% of respondents had a positive perception of the choice of chemical drugs, 60% of respondents had a positive perception of the choice of traditional drugs, and 53,75% of respondents had a positive perception of the choice of combination drugs (chemical and traditional) as well as a positive perception of selection of drugs, both chemical drugs and traditional drugs for hypercholesterolemia based on the Health Belief Model (HBM). In conclusion, the majority of Sukorejo people have a positive perception regarding the choice of chemical drugs and traditional medicines for hypercholesterolemia